2009
DOI: 10.1103/physrevlett.103.037201
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Lattice Order in FrustratedZnCr2O4

Abstract: Using synchrotron X-rays and neutron diffraction we disentangle spin-lattice order in highly frustrated ZnCr2O4 where magnetic chromium ions occupy the vertices of regular tetrahedra. Upon cooling below 12.5 K the quandary of anti-aligning spins surrounding the triangular faces of tetrahedra is resolved by establishing weak interactions on each triangle through an intricate lattice distortion. The resulting spin order is however, not simply a Néel state on strong bonds. A complex co-planar spin structure indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 23 publications
4
54
0
Order By: Relevance
“…Further studies conducted between the Curie-Weiss and Néel temperatures revealed the presence of negative thermal expansion below 100 K [16,23], shifting of the magnetic resonance line [20], anomalous behavior of eigenfrequencies of phonon modes [16], and deviation from Curie-Weiss behavior [1], making further investigation with muon spin-relaxation measurements attractive. The presence of local magnetic correlations is well established in the analogous oxide, ZnCr 2 O 4 [24][25][26], but it possesses, in contrast to selenide, a large negative Curie-Weiss constant. Therefore, the suppression of long-range magnetic order in ZnCr 2 O 4 (θ CW /T N = 32) is the result of inherent geometric frustration and not only from bond frustration.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies conducted between the Curie-Weiss and Néel temperatures revealed the presence of negative thermal expansion below 100 K [16,23], shifting of the magnetic resonance line [20], anomalous behavior of eigenfrequencies of phonon modes [16], and deviation from Curie-Weiss behavior [1], making further investigation with muon spin-relaxation measurements attractive. The presence of local magnetic correlations is well established in the analogous oxide, ZnCr 2 O 4 [24][25][26], but it possesses, in contrast to selenide, a large negative Curie-Weiss constant. Therefore, the suppression of long-range magnetic order in ZnCr 2 O 4 (θ CW /T N = 32) is the result of inherent geometric frustration and not only from bond frustration.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence these materials have emerged as canonical examples of the phenomenon of "order-by-distortion" in which magnetic frustration is relieved by a structural transition. [16][17][18][19] Calculations based on a classical effective model for the spins with coupling to the lattice predict a rich phase diagram in an applied magnetic field [20][21][22][23][24] which was observed in a series of remarkable experiments at fields up to 600T. [25][26][27][28][29] owen.benton@oist.jp Recently, a new class of magnetic materials has been synthesised which promises an interesting variation on this picture.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the highly frustrated chromites MgCr2O4, ZnCr2O4, CdCr2O4, and HgCr2O4 antiferromagnetic ordering sets in at the Néel temperatures TN = 12.9, 12.5, 7.8, and 5.8 K, respectively. [6][7][8][9] Due to the presence of magnetoelastic effects a change to a lower crystal structure symmetry was found at these temperatures which relieve the frustration and enabling the magnetic order. 7,8 by high-resolution x-ray synchrotron powder diffraction that the change from the tetragonal to an orthorhombic structure (space group Fddd) occurs concurrently with the onset of ferrimagnetic order.…”
Section: Introductionmentioning
confidence: 99%